206k views
0 votes
Please help!! What is 6(4 - y) = 5 + 3?

User StackTrace
by
4.3k points

2 Answers

3 votes

Answer: Hi!

First, we need to distribute 6 to the terms inside of the parentheses, 4 and -y.

6 * 4 = 24

6 * (-y) = -6y

Our equation now looks like this:

24 - 6y = 5 + 3

We can now combine like terms.

24 - 6y = 5 + 3

5 + 3 = 8

Our equation now looks like this:

24 - 6y = 8

We can now use inverse operations to get rid of 24. Remember, our goal is to isolate the x. The inverse operation for addition (24 is positive) is subtraction, so we subtract 24 on both sides:

24 - 6y = 8

- 24 - 24

Our equation now looks like this:

-6y = -16

Last step! We now use inverse operations to get rid of -6. The inverse operation for multiplication is division (-6 is being multiplied by y); so we divide -6 on both sides.

-6y/-6 = y

-16/-6 = 8/3 = 2 2/3

Our equation now looks like this:

y = 2 2/3

Therefore, your solution is 2 2/3.

Hope this helps!

User Anton Dergunov
by
6.6k points
2 votes

Answer:


\boxed{ \boxed{ \bold{ \sf{2.6}}}}

Explanation:


\sf{6(4 - y) = 5 + 3}

Distribute 6 through the parentheses


\sf{24 - 6y = 5 + 3}

Add the numbers


\sf{24 - 6y = 8}

Move constant to right hand side and change it's sign


\sf{ - 6y = 8 - 24}

Calculate


\sf{ - 6y = - 16}

Divide both sides of the equation by -6


\sf{ ( - 6y)/( - 6) = ( - 16)/( - 6) }

Calculate


\sf{y = 2.6}

Hope I helped!

Best regards!!

User Aecend
by
4.3k points